ANALISIS KESENJANGAN DAN UPAYA PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA DI DIREÇÃO NACIONAL DE METEOROLOGIA E GEOFÍSICA (DNMG) TIMOR-LESTE SEBAGAI BAGIAN PEMENUHAN KEPATUHAN PADA JARINGAN DASAR PENGAMATAN GLOBAL (GBON) - Redha Nugraheni, Imma; Wandayantolis, Wandayantolis; Nurhayati, Nurhayati (Jurnal Widya Climago, 2023)
GBON is a global network system that provides weather data for weather forecasters and climate experts worldwide. However, there are still developing countries, such as Timor-Leste, that have yet to meet the GBON requirements. This paper delves into the gap between the current conditions at DNMG, an institution that provides meteorology, climatology, and geophysics services in Timor-Leste, and the conditions required to comply with GBON requirements in terms of organizational governance, observation infrastructure, and human resource capacity. The study used a qualitative method with a descriptive approach, and data was obtained from interviews with key figures involved in the Systematic Observation Financing Facility framework. The analysis reveals that the DNMG organization's position as a technical directorate in the Ministry of Transport and Communications of Timor-Leste limits its authority in budget planning and organizational development. Despite meeting the horizontal resolution of the basic surface observation requirements for Timor-Leste as a Small Island Developing States (500 km), the poor condition of the equipment and the failure to exchange data internationally prevent Timor-Leste from complying with GBON. Furthermore, limited number and capacity of human resources and the absence of Standard Operating Procedures hinder effective work processes within DNMG. To increase the capacity of DNMG human resources, BMKG actively provides assistance and support to DNMG Timor-Leste in the form of training activities and workshops to meet the observation and service standards required in GBON. Keywords: GBON, gap analysis, organizational governance, observation infrastructure, human resources